Dispelling the shadow of fiscal dominance? Fiscal and monetary announcement effects for euro area sovereign spreads in the corona pandemic - Annika Havlik; Friedrich Heinemann; Samuel Helbig; Justus Nover (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We use event study regressions to compare the impact of EU monetary versus fiscal policy announcements on government bond spreads of ten euro member countries. Our motivation is to evaluate which of the two players - the ECB or the EU fiscal level - has been more crucial for the stabilization of euro sovereign bond markets in the crisis environment of the pandemic. This question is of substantial relevance to assess potential risks for the effective independence of the ECB in the future. Our key result is that the pandemic monetary emergency measures through the PEPP have been highly effective, whereas fiscal rescue announcements had much less impact. We document a smaller and statistically significant spread-reducing effect only for the announcement of the 'Next Generation EU' program. In contrast, a temporary relaxation of European fiscal rules through the activation of the emergency-escape clause under the Stability and Growth Pact is associated with rising spreads. Our results have an unpleasant implication for the debate on a looming fiscal dominance of the ECB in the presence of rising public debt levels as so far, the stabilization of sovereign bond markets appears to hinge largely on the Eurosystem's role as a massive buyer of high-debt countries' sovereign bonds.
Keywords: E63; H12; H63; H81; 330; Sovereign spreads; monetary policy; fiscal policy; fiscal dominance; event analysis